DIMENSIONAL ACCURACY OF 3D PRINTED DOG BONE STRUCTURES - Nugroho, Wendy Triadji; Tyagita, Dicky Adi; Wahyudiono, Arif; Suranto, Dwi Djoko (Jurnal Rekayasa Mesin, 2025)
The current study provides a comprehensive discussion regarding statistical analysis of dimensional accuracy comprising thickness, gauge section width, circularity and cylindricity for 3D printed polylactic acid (PLA) specimens according to the dimensional specifications of ASTM D638 standard type IV, which are optimally built via fused deposition modelling (FDM). This work focuses on investigating the primary influences of 3D printing parameters as input factors consisting of nozzle temperature, infill density as well as layer height on dimensional deviation of the printed specimens. The confirmation tests are implemented in this study to ensure the experimental work's reproducibility. The resulting data shows that layer height dominates the effects, namely 80, 88, 81 and 81% on thickness, gauge section width, circularity and cylindricity. Meanwhile, nozzle temperature gives the second considerable influence on dimensional deviation of printed specimens, around 16, 9, 16 and 17%. Conversely, infill density promotes a negligible effect on the dimensional error of such specimens. Furthermore, the confirmation tests indicate that the experimental works are highly reproducible. These findings can contribute significantly to the additive manufacturing technology for PLA material, especially when the printed specimens are used for specific applications in biomedical, engineering and aerospace fields.